120k views
4 votes
Solve the equation for y

6=4x+9y

User Toon Lite
by
5.1k points

1 Answer

2 votes

Answer:

y=
-(4x)/(9) +
(2)/(3)

Explanation:

6=4x+9y

First swap sides so that all variables are on the left side.

4x+9y=6

Subtract 4x from both sides.

9y=6-4x

Divide both sides by 9, this undoes the multiplication.

y=
(6-4x)/(9)

Divide 6-4x by 9.

y=
-(4x)/(9) +
(2)/(3)

hope this helps!

User Haqqi
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.